Answer:
x = 2 and -4
Step-by-step explanation:
(x + 1)² = 9
First, take the square root of both sides. This will eliminate the square on the left side.
(x + 1) = √9
Note that √9 can be 3 or -3.
Let's write out both possibilities.
(x + 1) = 3
(x + 1) = -3
Solve.
(x + 1) = 3
[subtract 1 from both sides]
x = 2
--
(x + 1) = -3
[subtract 1 from both sides]
x = -4
Your answers are 2 and -4.
Let's check our answers by plugging in the values back into the original equation.
(x + 1)² = 9
(2 + 1)² = 9
(3)² = 9
9 = 9
That solution is correct.
(x + 1)² = 9
(-4 + 1)² = 9
(-3)² = 9
9 = 9
That solution is also correct.
Your answer is correct.
Hope this helps!